Effect of N-Terminal Peptide Modifications on In Vitro and In Vivo Properties of 177Lu-Labeled Peptide Analogs Targeting CCK2R - Anton Amadeus Hörmann; Maximilian Klingler; Christine Rangger; Christian Mair; Lieke Joosten; Gerben M. Franssen; Peter Laverman; Elisabeth von Guggenberg (MDPI AG, 2023)
The therapeutic potential of minigastrin (MG) analogs for the treatment of cholecystokinin-2 receptor (CCK2R)-expressing cancers is limited by poor in vivo stability or unfavorable accumulation in non-target tissues. Increased stability against metabolic degradation was achieved by modifying the C-terminal receptor-specific region. This modification led to significantly improved tumor targeting properties. In this study, further N-terminal peptide modifications were investigated. Two novel MG analogs were designed starting from the amino acid sequence of DOTA-MGS5 (DOTA-DGlu-Ala-Tyr-Gly-Trp-(N-Me)Nle-Asp-1Nal-NH2). Introduction of a penta-DGlu moiety and replacement of the four N-terminal amino acids by a non-charged hydrophilic linker was investigated. Retained receptor binding was confirmed using two CCK2R-expressing cell lines. The effect on metabolic degradation of the new 177Lu-labeled peptides was studied in human serum in vitro, as well as in BALB/c mice in vivo. The tumor targeting properties of the radiolabeled peptides were assessed using BALB/c nude mice bearing receptor-positive and receptor-negative tumor xenografts. Both novel MG analogs were found to have strong receptor binding, enhanced stability, and high tumor uptake. Replacement of the four N-terminal amino acids by a non-charged hydrophilic linker lowered the absorption in the dose-limiting organs, whereas introduction of the penta-DGlu moiety increased uptake in renal tissue.